Percepción docente sobre las dificultades iniciales de aprendizaje en estudiantes del tercer grado de primaria de una institución educativa del Callao - Salazar Sandoval, Marita Rosel (2012)
The following research gives the researcher`s point of view about the initial learning disabilities in third grade elementary school students in a school in Callao. Bravo`s ( 1979 ) questionary for learning disabilities was applied to 85 children. The results shows that the evaluated dimensions such as receptive information ,attention , and memory mistakes on writing and math mistakes most of the students are in an intermediate level . The main point is that a significant group of 42% of students are in a higher level . Also it was evaluated how fast they can learn mathematics and language according to the teaching perception students are in an intermediate level 74 % and the intelligence capacity is high 84% according to the teaching perception.